Prevalensi Antibodi IgG dan DNA Cytomegalovirus pada darah donor di unit transfusi darah Provinsi DKI Jakarta - Ganjar Noviar; Ni Ken Ritchie; Budiman Bela; Yuyun SM Soedarmono (Balai Litbangkes Tanah Bumbu, 2017)
Indonesia has not conduct regular screening test of CMV infection due to the lack of seropositive prevelance data information. However, seronegative CMV results is not an indicator of safe blood for transfusion, so that another test that serves as confirmation test for CMV DNA is required. The aim of this study is to obtain prevalence data of CMV IgG antibody positive, the prevalence of CMV DNA positive and to determine the effect of CMV IgG titers against CMV DNA in blood donors in UTD PMI DKI Jakarta. Cross-sectional method was used to test 113 blood donor samples which have met inclusion criteria. Screening for CMV IgG antibody was held using indirect method chemiluminescence immunoassay (ChLIA) by Liason® XL 10050 Chemiluminescence Analyzer and CMV DNA analysis using qPCR method for the detection of CMV UL 54 with a tool Roche Light Cycler 480 II. Results indicate positive prevalence of IgG CMV in 111 samples (98.23%), and negative CMV IgG in 2 samples (1.77%). Prevalence of CMV DNA positive donors is one sample (0.88%), 112 negative CMV DNA samples (99.12%) and Fisher's test results P (0.982)> α (0.05) showed no significant association between CMV IgG status with CMV DNA. CONCLUSIONS: UTD DKI Jakarta has a high prevalence of CMV IgG with low prevalence of CMV DNA.